Drums, Hearts, Bulls, and Dead Gods: The Theology of the Ancient Mesopotamian Kettledrum - Gabbay, Uri (Journal of ancient Near Eastern religions, 2018)
The article deals with the theology of the lilis kettledrum, used to accompany prayers in ancient Mesopotamian temple cult. The article analyzes the ritual in which the head of the kettledrum was covered with the hide of a bull and the ancient commentary on this ritual, showing that the ancient understanding of this ritual was that it reflected the primordial battle between the gods Enlil and Enmešara over the rule of the universe. The article connects this myth to other mythical episodes, such as the myths of the Bull of Heaven, Anzu, and Atra-ḫasīs. The analysis of these materials leads to the conclusion that the playing of the kettledrum during the performance of ancient Mesopotamian prayers symbolized the beating heart of the deities to whom the prayers were addressed.